Ecophilosophical Message of Encyclical Laudato Si’ - Bołoz, Wojciech; Jaromi, Stanisław; Karaczun, Zbigniew; Łepko, Zbigniew; Papuziński, Andrzej; Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2016)
In the encyclical Laudato Si’ Pope Francis summarizes the rich legacy of his predecessors contained in the statements on the ecological question. Starting from Paul VI, successive popes repeatedly referred to the issue in different contexts and aspects. Pope Francis’s standpoint actively involved the community of the Catholic Church in the mainstream of contemporary environmental debate, demonstrating full readiness for the broadest cooperation in research and activities inspired by concern for the Earth, our common home. The Pope sees the possibility of such cooperation in consultation with all people of good will who share the appreciation for the set of issues presented in this paper: idea of sustainable development, idea of integral ecology, bioethical issues, climate change issue, and eco- -justice issue.